How Business Studies Address Sustainability Consciousness: A Bibliometric Analysis - Desi Elvera Dewi; Joyo Winoto; Noer Azam Achsani; Suprehatin (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: Sustainability has emerged as one of the most critical global challenges, making its integration into business studies, essential. Business studies play a crucial role in shaping leaders amid escalating global challenges, such as climate change, inequality, and resource degradation. However, current curricula often emphasize technical knowledge over the deeper ethical and cognitive dimensions required for sustainable decision making. Traditional business programs have been criticized for creating a disconnect between business practices and ethical accountability. Furthermore, business curricula often fail to fully integrate the ethical shifts necessary to internalize sustainability as a core value.Purpose: To map the trends, patterns, and gaps in the literature on sustainability consciousness in business studies, with a particular focus on identifying how this concept has been addressed in previous research.Design/methodology/approach: A bibliometric analysis was conducted on 2,767 Scopus-indexed publications (1993–2022) using VOSviewer to identify trends and gaps in sustainability consciousness research in business studies. The problem formulation was guided by the PICO framework to define the key elements of the research question in academic research studies.Findings/Result: Although sustainability topics in business studies are widely studied, research on “sustainability consciousness” remains underexplored. Keywords such as ‘consciousness” and “awareness” are absent from the central clusters, highlighting a significant gap in the literature. This finding indicates that, despite extensive research on sustainability, there is a limited focus on addressing the concepts of consciousness and awareness within business studies research.Conclusion: There is a significant gap in integrating sustainability consciousness into business education. Current curricula lack an emphasis on the ethical, cognitive, and affective aspects of sustainability.Originality/value (State of the art): This study is one of the first to map the research landscape of sustainability consciousness in business studies. By identifying this gap, this study contributes to the growing body of knowledge by highlighting the urgent need for a holistic approach that emphasizes sustainability consciousness in business education and practice. Keywords:    bibliometric analysis, business study, curriculum integration, sustainability awareness, sustainability consciousness